What Makes a Small Farm Successful? A Review of Success Factors, Needs, and Challenges - Katie Tritsch; Ken Mix; Michelle L. Edwards; Manuel Piña ([TEST] Journal of Extension, 2021)
Small-scale farmers face unique challenges. In this review, we conceptualize small farm success by aggregating and categorizing results from recent (post-2000) literature on small farm success factors and producer needs assessments. Our findings suggest that small farm success is multifaceted and not limited to profitability. We find that small farms have a diverse range of needs, though little has been done to rank their importance. We conclude that future research would benefit from increased methodological transparency and a systematic approach to needs evaluation. We consider the role of Extension professionals regarding the continued success of small farms.
Keywords: small farms; small-scale producers; farm success; success factors; needs assessments